Molecular Recognition of DNA Double Helix Gene Regulation and Photochemistry of BrU Substituted DNA - Saha, Abhijit (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
In this book, the molecular recognition of DNA using small molecules is discussed, with a study of the photochemistry of BrU-labeled DNA. The purposes of the study were to develop small molecules for regenerative medicine, to develop a method to detect the recognition site of small molecules, and to detect the most important biological phenomena using the photochemistry of BrU-labeled DNA. The study began with the design and development of small molecules that can induce pluripotency genes. To deal with the important issue of cell permeability of the original compound, a new analogue of the original with improved gene expression was designed and synthesized. Using the photochemistry of BrU-labeled DNA, crucial biological phenomena such as cooperativity between transcription factors were detected. For the first time, the cooperativity was examined by excess electron transfer assay. DNA was also studied very carefully in order to understand the mechanism of the double-strand break in the UVA micro-irradiation technique. The mechanism of the double strand remained untouched. Nevertheless, the double-strand break mechanism was clearly demonstrated by Hoechst dye, as shown in this book. .